Butoh and Suzuki Performance in Australia : Bent Legs on Strange Grounds, 1982-2023 - Marshall, Jonathan W., (Australian Playwrights ;, 2025)
In Butoh and Suzuki Performance in Australia: Bent Legs on Strange Grounds, 1982-2023 , Marshall considers how the originally Japanese forms of butoh dance and Suzuki's theatre reconfigure historical lineages to find ancient yet transcultural ancestors within Australia and beyond. Marshall argues that artists working in Australia with butoh and Suzuki techniques develop conflicted yet compelling diasporic, multicultural, spiritually and corporeally compelling interpretations of theatrical practice. Marshall puts at the centre of butoh historiography the work of Tess de Quincey, Yumi Umiumare, Tony Yap, Lynne Bradley, Simon Woods, Frances Barbe, and Australian Suzuki practitioners Jacqui Carroll and John Nobbs. Jonathan W. Marshall's Bent Legs on Strange Grounds is an important contribution to the body of literature on butoh, as well as to studies of dance in Australia that will be valuable to practitioners and scholars alike. Detailed discussions of Australian butoh artists open up consideration of how global and local histories, migrations, and landscapes not only were key to butoh's formation in Japan, but also to its continued development around the world. Attention to butoh's emplacement in Australia, Marshall convincingly argues, reveals insights about national identity, race, power, and more that are relevant well beyond the Australian performance context. - Rosemary Candelario, Texas Woman's University, co-editor, Routledge Companion to Butoh Performance (2018) Marshall's Bent Legs on Strange Grounds explores the remarkable transformative era of Australia's reconsideration of its place in the region. A definitive study of Australian experiments in butoh and the theatrical vision of Suzuki Tadashi, the book shows how new corporeal and spatial dramaturgies of the Japanese avant-garde fundamentally changed Australian performance. Expansively researched and annotated, this impressive study connects Australian performance after the New Wave with globalization, postmodern dance, Indigeneity, and subcultures, and it details the work of leading Australian/Asian artists. Bent Legs on Strange Grounds speaks about the development of embodied knowledge and the consequential refiguration of Australia's sense of being in the world. It is also a study of butoh and Suzuki's legacy in global terms, wherein Australian experimental performance also becomes something larger than itself. - Peter Eckersall, The Graduate Center, CUNY, author of Performativity and Event in 1960s Japan (2013).